1994
DOI: 10.1161/01.res.74.4.669
|View full text |Cite
|
Sign up to set email alerts
|

Immunologic identification of Na+,K(+)-ATPase isoforms in myocardium. Isoform change in deoxycorticosterone acetate-salt hypertension.

Abstract: There are three isoforms of the catalytic (alpha) subunit of the Na+,K(+)-ATPase, each derived from a different gene, that differ in their sensitivity to inhibition by cardiac glycosides. Antibodies specific for the three isoforms were used to study Na+,K(+)-ATPase isoform expression in ventricular myocardium, where an understanding of digitalis receptor diversity is most important. In the rat heart, there is simultaneous expression of two isoforms in adult ventricle, and immunofluorescence studies demonstrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
77
0

Year Published

1996
1996
2011
2011

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(83 citation statements)
references
References 51 publications
6
77
0
Order By: Relevance
“…The K1 ⁄2 values for internal Na ϩ measured in this study for human ␣1 and ␣2 isozymes are in the same range than those previously reported for human kidney (33) and red blood cells (34). A low Na ϩ affinity component corresponding to the ␣3 isoforms has not been observed in human heart (35) probably because ␣3 isoforms represent only a small fraction of the total ␣ subunit population in this tissue (36,37). In contrast to data on K ϩ activation, our data on Na ϩ activation of different human Na,K-ATPase isozymes compare well with data obtained for rat isozymes (for review, see Ref.…”
Section: Nak-atpase Isozymessupporting
confidence: 81%
See 1 more Smart Citation
“…The K1 ⁄2 values for internal Na ϩ measured in this study for human ␣1 and ␣2 isozymes are in the same range than those previously reported for human kidney (33) and red blood cells (34). A low Na ϩ affinity component corresponding to the ␣3 isoforms has not been observed in human heart (35) probably because ␣3 isoforms represent only a small fraction of the total ␣ subunit population in this tissue (36,37). In contrast to data on K ϩ activation, our data on Na ϩ activation of different human Na,K-ATPase isozymes compare well with data obtained for rat isozymes (for review, see Ref.…”
Section: Nak-atpase Isozymessupporting
confidence: 81%
“…On the other hand, ␣3 isozymes found in neuronal cells and which have a low Na ϩ affinity, may be suited to restore intracellular Na ϩ concentrations after a series of action potentials. The presence of the 3 ␣ isoforms in human cardiomyocytes (36,37) indicates that ion homeostasis is also finely regulated in these cells and that, as in skeletal muscles and neurons, the 3 Na,KATPase isozymes may act in concert to meet the physiological needs.…”
mentioning
confidence: 99%
“…This notion was consistent with the result of fractionation which revealed that the distribution of N-cadherin among the fractions of guinea-pig heart homogenates was similar to that of the β2 subunit rather than that of the β1. Although the α3 subunit has been reported to be present in the hearts of humans [22] and dogs [23], its distribution in the ventricular myocytes and corresponding β subunits for heterodimer formation have not yet been elucidated. As a result, the present experiment extended Zahler et al's findings [21] and also demonstrated for the first time, the presence of the α3β2 isozyme in the intercalated disc of ventricular myocytes.…”
Section: Distribution and Combination Of A And B Subunitsmentioning
confidence: 99%
“…␣1 is almost ubiquitously distributed, whereas ␣2 is expressed strongly in muscle (skeletal, smooth, and cardiac) and astrocytes, ␣3 primarily in nerve cells, and ␣4 only in spermatozoa. Human heart expresses ␣1, ␣2, and ␣3 isoforms and ␤1 (13). In cardiac myocytes, ␣2 is concentrated in the T-tubules adjacent to the SR, 3 whereas ␣1 is more evenly distributed in T-tubules and SR (14).…”
mentioning
confidence: 99%